2013
DOI: 10.5565/rev/elcvia.516
|View full text |Cite
|
Sign up to set email alerts
|

3D Segmentation for Multi-Organs in CT Images

Abstract: The study addresses the challenging problem of automatic segmentation of the human anatomy needed for radiation dose calculations. Three-dimensional extensions of two well-known stateof-the art segmentation techniques are proposed and tested for usefulness on a set of clinical CT images. The new techniques are 3D Statistical Region Merging (3D-SRM) and 3D Efficient Graph-based Segmentation (3D-EGS). Segmentations of eight representative tissues (lungs, stomach, liver, heart, kidneys, spleen, bones and the spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…When compared to previous multi-organ segmentation studies, the results of this study are comparable or better. A multi-organ segmentation study using statistical region merging method reported DSC values of 0.95 for lungs, 0.93 for heart and kidneys, an average of 0.90 for liver and spleen, and an average of 0.86 for spinal cord and bones for a single adult test patient (Bajger et al 2013). A study using entangled decision trees reported an overall Jaccard overlapping index of 56% for eight organs from 50 patient scans from various CT vendors (Montillo et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…When compared to previous multi-organ segmentation studies, the results of this study are comparable or better. A multi-organ segmentation study using statistical region merging method reported DSC values of 0.95 for lungs, 0.93 for heart and kidneys, an average of 0.90 for liver and spleen, and an average of 0.86 for spinal cord and bones for a single adult test patient (Bajger et al 2013). A study using entangled decision trees reported an overall Jaccard overlapping index of 56% for eight organs from 50 patient scans from various CT vendors (Montillo et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The segmentation of multiple organs using standard graph-based approaches has been successfully explored for the abdominal and thoracic region (Bajger et al, 2013;Dong et al, 2016;Linguraru and Summers, 2014). However, the bottom-up approach used in these models presents an important limitation: the need for additional constraints to ensure the anatomical consistency of the results in a complex multi-organ scenario.…”
Section: Graph-based Modelsmentioning
confidence: 99%
“…GlM► Smyth et al, 1997; MuLeM► Bernard et al, 2001;Lecron et al, 2012a;Lecron et al, 2012b;Neubert et al, 2014;SeqM► de Bruijne et al 2007; ArtM► Ali et al, 2012;Bois et al, 2005;Boisvert et al, 2006;Boisvert et al, 2008a;Boisvert et al, 2008b;Desroches et al, 2007;Gill et al, 2012;Harmouche et al, 2012;Kadoury and Paragios, 2009;Klinder et al, 2008;Monheit and Badler, 1991;Moura et al, 2011;Panjabi et al, 1976;Rasoulian et al, 2013 SeqM► Camara et al, 2004;He et al, 2015;Kéchichian et al, 2014;Matsumoto and Udupa, 2013;Sun et al, 2016;Udupa et al, 2011;Udupa et al, 2013;Wang et al, 2014a;Wang et al, 2014b;MaLrM► Criminisi et al, 2009;Iglesias et al, 2011;Keraudren et al, 2015;Mansoor et al, 2017;Mansoor et al, 2018;Montillo et al, 2011;Pauly et al, 2011;de Vos et al, 2017; AtM► Gubern-Mérida et al, 2011;Schreibmann et al, 2014; GrM► Bajger et al, 2013;Kéchichian et al, 2014; Heart GlM►…”
Section: Head and Neckunclassified